Wakefield acceleration based on high power pulsed lasers and electron beams (overview) - Onishchenko, I.N. (Вопросы атомной науки и техники, 2006)
The physical principles are considered on intense wakefields excitation in plasma and dielectric by high-power
short laser pulse or by a train of electron bunches for high-gradient acceleration of charged particles with purpose to
elaborate the concept of future compact accelerators for high-energy physics and high technology applications, and
also for creation of contemporary short pulsed radiation sources. The results of investigations on laser’s acceleration
in vacuum, electrons acceleration in plasma by high power laser pulse with obtaining beams of small angle and energy
dispersion, concepts of plasma and dielectric wakefield accelerators are presented. The perspective research
program of the schemes of laser/beam acceleration in plasma and dielectric is considered. Излагаются физические принципы возбуждения интенсивных кильватерных полей в плазме и других средах мощным коротким лазерным импульсом или последовательностью релятивистских электронных сгустков для высоко-градиентного ускорения заряженных частиц с целью разработки концепции будущих компактных ускорителей для физики высоких энергий и ряда высокотехнологичных приложений, а также для создания современных коротко-импульсных источников излучения. Представлены результаты исследований по лазерному ускорению частиц в вакууме, ускорению электронов в плазме мощным лазерным импульсом и получению пучков с малым угловым и энергетическим разбросом, ускорению электронов плазменными и диэлектрическими кильватерными полями, возбуждаемыми релятивистскими электронными сгустками. Излагается перспективная программа исследований схем лазерного и пучкового ускорения в плазме и диэлектрике. Викладені фізичні принципи збудження інтенсивних кільватерних полів у плазмі та інших середовищах
потужним коротким лазерним імпульсом або послідовністю релятивістських електронних згустків для
високо-градієнтного прискорення заряджених частинок з метою розробки концепції майбутніх компактних
прискорювачів для фізики високих енергій і ряду високотехнологічних застосувань, а також для створення
сучасних коротко-імпульсних джерел випромінювання. Представлені результати досліджень по лазерному
прискоренню часток у вакуумі, прискоренню електронів у плазмі потужним лазерним імпульсом і
отриманню пучків з малим кутовим і енергетичним розкидом, прискоренню електронів плазмовими та
діелектричними кільватерними полями, збуджуваними релятивістськими електронними згустками.
Наводиться перспективна програма досліджень схем лазерного та пучкового прискорення у плазмі і
діелектрику.